SYNTHETIC PYRIDINE SUBSTITUTED AMINO ACIDS AND THEIR DERIVATIVES: DOI: https://doi.org/10.17721/1728-2209.2019.1(56).5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
This paper reports on the synthesis of new derivatives of ε-aminocaproic and γ-aminobutyric acid modified with a pyridin-2-yl substituent at the ω-position of the main chain.The hemostatic activity of both ε-aminocaproic acid itself and its various synthetic analogues is widely known. Likewise, numerous γ-aminobutyric acid derivatives are strong neurotransmitters extensively used in the treatment of the nervous system disorders. No less popular are biologically active substances containing a pyridine or piperidine fragment; among which there are antibiotics, antimalarial, anti-sclerotic and anti-allergic drugs, as well as anti-depressants and analgesics.Therefore, the introduction of the pyridine fragment into the amino acid structures is interesting in terms of their potential biological activity investigation.So, a method for the synthesis of 5-amino-5-(pyridin-2-yl)pentanoic and 6-amino-6-(pyridin-2-yl)hexanoic acid has been developed by us. The proposed scheme is based on the available reagents using. The key stage is the Schmidt rearrangement of 2-(pyridin-2-yl)cyclopentanone and 2-(pyridin-2-yl)cyclohexanone, previously synthesized from pyridine N-oxide and cycloalkenyl morpholinide. For synthesized pyridine substituted cycloalkanones according to NMR spectroscopy, the presence of keto-enol tautomerism was established.As a result of Schmidt rearrangement, lactams (2-(pyridin-2-yl)piperidone and 2-(pyridin-2-yl)azepanone) are formed, and the last ones had been hydrolyzed in an acidic medium to open the lactam cycle. Thus, 5-amino-5-(pyridin-2-yl)pentanoic and 6-amino-6-(pyridin-2-yl)hexanoic acid were isolated as hydrochlorides and the hydrochlorides were converted to the zwitterion form using propylene oxide.The first stage of the developed scheme (preparation of pyridylalkanones) occurs in rather low yields, about 35 %. But, after the rearrangement, hydrolysis and the formation of zwitterion do not cause difficulties and are characterized by high yields. Consequently, the proposed synthetic sequence is preparatively advantageous.
Keywords: synthetic δ- and ε-amino acids, Schmidt rearrangement, picolyl-2-amine.